Instagram Use in Education: Trends, Themes and Bibliometric Findings - Yelmen, Merve Gülmüş; Özek, Müzeyyen Bulut; Kalemkuş, Fatih (My University, 2025)
Today, social media tools are increasingly playing a role in learning processes. Instagram, which is a visual and interactive tool in particular, stands out as one of the tools that support learning. Thus, assessing the state of Instagram studies in educational research today helps to imagine the future. Therefore, in this study, studies published on the use of Instagram in education were examined using the bibliometric analysis method. In the study, 836 academic studies published between 2015-2024 in the Web of Science (WoS) database were analyzed. The findings obtained show that research in this field has increased rapidly, especially since 2020. It has been determined that studies are focused on the use of Instagram in higher education as well as in education such as medical education and language learning. In addition, the USA stands out as the country with the most publications in articles published on the use of Instagram in education, followed by Spain and the UK. In addition to these findings, the “Cureus Journal of Medical Science” stands out as a journal in terms of the frequency of published articles, while the “University of Barcelona” stands out in terms of institutions. On the other hand, although “Li JW” stands out as the most published author among the authors who published articles on the use of Instagram in education, “Elizabeth R. Lyden” stands out as the most cited author and the author who is in a central position with extensive collaboration. The research findings were evaluated in the context of the literature and some suggestions were made.
Keywords: Instagram; education; social media; bibliometric analysis; social media application